2019
DOI: 10.1042/bsr20181776
|View full text |Cite
|
Sign up to set email alerts
|

Increase of glandular epithelial cell clusters by an external volume expansion device promotes adipose tissue regeneration by recruiting macrophages

Abstract: Background: There is a clinical need for the use of engineered adipose tissue in place of surgical reconstruction. We previously found that the external volume expansion (EVE) device increased special cell clusters in well-vascularized connective stroma during adipose regeneration. However, the origin of these cell clusters and their role in adipose tissue regeneration remain unknown. Aim: In the present study, we evaluated EVE in the construction of expanded prefabricated adipose tissue (EPAT) in a rat model.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 41 publications
1
6
0
Order By: Relevance
“…The mRNA levels of the total macrophage marker Mac-2 [ 4 , 5 ] in wild-type mice and PD-1 −/− mice were significantly higher than those in the noninjured group at 1, 3, 7, and 14 days after injury ( P < 0 05). However, there was no significant difference between the PD-1 −/− and wild-type mice ( P > 0.05) (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The mRNA levels of the total macrophage marker Mac-2 [ 4 , 5 ] in wild-type mice and PD-1 −/− mice were significantly higher than those in the noninjured group at 1, 3, 7, and 14 days after injury ( P < 0 05). However, there was no significant difference between the PD-1 −/− and wild-type mice ( P > 0.05) (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…We studied this issue. In the present study, Mac-2 was used as a marker of total macrophages [ 4 , 5 ], iNOS and CD86 were used as pro-inflammatory macrophage markers [ 14 , 15 ], and Arg1, CD206, and CD163 were used as anti-inflammatory macrophage markers [ 14 , 15 ]. The present study found that the number of total macrophages, pro-inflammatory macrophages, and anti-inflammatory macrophages increased in the early stage (1–3 days) of skeletal muscle injury in wild-type mice.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Proteins were extracted from cultured cells or tissues, and Western blot analyses of the extracted proteins were performed with the enhanced chemiluminescence (ECL) system (Thermo Fisher Scientific) [7, 21]. Blots were probed with anti‐DGKθ (Proteintech Group), anti‐APOC3 and anti‐PPARα (Wanlebio), anti‐HNF1B (HUABIO), anti‐glyceraldehyde‐3‐phosphate dehydrogenase (GAPDH; Engibody Biotechnology, Inc.), and goat anti‐mouse immunoglobin G (IgG) and goat anti‐rabbit IgG (horseradish peroxidase, ZSGB‐BIO).…”
Section: Methodsmentioning
confidence: 99%
“…EVE was shown to generate specific cell clusters. 100 These clusters contained glandular epithelial-like cells, as evidenced by their gland-like structure and expression of specific markers. Soon after their generation, these cell clusters began to secrete monocyte chemoattractant protein-1 (MCP-1), which induced infiltration of significant numbers of macrophages.…”
Section: Induction Of Angiogenesis In Adipose Tissues By Evementioning
confidence: 99%